Decomposing the Poor-Non-Poor Gap in the Prevalence of Undiagnosed and Untreated Hypertension Among Bangladeshi Population - Mosiur Rahman; Mahfuza Khatun; Asrafun Naher Pinkey; Syed Emdadul Haque; Farhana Akhter Liza; Md. Nuruzzaman Haque; Prosannajid Sarkar; Tapan Kumar Roy; G. M. Rabiul Islam; Md. Rashed Alam; Mahmudul Hasan; Izzeldin Fadl Adam; et al. (Global Heart)
Objectives: Our objectives were to ascertain: the prevalence and socio-economic distribution of hypertension, as well as the rates of undiagnosed and untreated hypertension; the association between socioeconomic status (SES) and the occurrence of hypertension, as well as the rates of undiagnosed and untreated hypertension; and the factors influencing the poor-non-poor gap in terms of the prevalence, diagnosis, and treatment of hypertension. Design: Cross-sectional nationally representative study. Methods: Data from the 2017–18 Bangladesh Demographic Health Survey were used. 11,776 participants who were 18 years of age or older responded to our analysis. We used the wealth index as a proxy for SES. The prevalence of hypertension, both diagnosed and undiagnosed, as well as its untreated states, were the outcome variables. Results: The age-adjusted prevalence of hypertension, undiagnosed as having hypertension, and untreated cases were 25.1%, 57.2%, and 12.3%, respectively. People in the poor SES groups had a 0.88 times (95% confidence interval [CI] 0.77–0.99) lower likelihood of having hypertension compared to those in the non-poor SES group. Individuals belonging to the poor SES group exhibited a likelihood of 1.68 and 1.53 times greater for having untreated hypertension and being undiagnosed with the condition, respectively, compared to those in the non-poor SES group. The results indicated that BMI played a role in increasing the disparity between the poor and non-poor populations concerning hypertension risk. Additionally, factors such as age, gender, and education were found to exacerbate the gap in the risk of undiagnosed hypertension between these two groups. Conclusion: The results of this study suggest that appropriate policy measures be developed for ongoing care and early identification, especially for older adults, men, and individuals with low levels of education from low socioeconomic backgrounds. Additionally, efforts must be made to reduce the prevalence of overweight and obesity among people in the non-poor SES category.